2017
DOI: 10.1515/biolog-2017-0165
|View full text |Cite
|
Sign up to set email alerts
|

Relations between tree canopy composition and understorey vegetation in a European beech-sessile oak old growth forest in Western Romania

Abstract: The diversity relationship between tree and herb layer has often been investigated, but the results are contradictory. Moreover, few studies of deciduous European species have been conducted to date in natural or near-natural forests, while such studies in old-growth forest with considerable co-dominance of oak are missing.In one of the best preserved natural European beech-sessile oak forests (Runcu-Grosi Natural Reserve, Western Romania) we investigated whether there is a correlation between canopy-layer div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Therefore, our findings suggested that in the mixed beech stand due to the low ratio of litter decomposition, release of nitrogen (Kooch, Sanji & Tabari, 2019) was lower than in the mixed hornbeam stand. Dölle et al (2017) confirmed that there was a positive significant correlation between the thickness of litter layer and beech dominance in the overstory stratum in the European beech stand. Bakhshandeh Navroud et al (2018) found that an increase in the beech frequency resulted in diminished soil carbon and nitrogen content.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Therefore, our findings suggested that in the mixed beech stand due to the low ratio of litter decomposition, release of nitrogen (Kooch, Sanji & Tabari, 2019) was lower than in the mixed hornbeam stand. Dölle et al (2017) confirmed that there was a positive significant correlation between the thickness of litter layer and beech dominance in the overstory stratum in the European beech stand. Bakhshandeh Navroud et al (2018) found that an increase in the beech frequency resulted in diminished soil carbon and nitrogen content.…”
Section: Discussionsupporting
confidence: 64%
“…Our finding demonstrated that the overstory compositional dissimilarities in the mixed beech stand and mixed hornbeam stand had led to differences in the herb-layer vegetation, which is in line with the findings of Koojiman and Cammeraat (2010) in the Netherlands' forests. The composition of understory vegetation is influenced by tree species in the overstory stratum (Rawlik, Kasprowicz, & Jagodzinski, 2018;Dölle, Petritan, Biris, & Petritan, 2017). Gilliam et al (2007) stated that the composition of the overstory layer directly or indirectly affects the understory species by changing light availability, moisture and soil fertility.…”
Section: Discussionmentioning
confidence: 99%
“…For above is possibly that the forest studied could be a beech-oak forest (F. grandiflora subsp. mexicana and Q. delgadoana) with particular process to coexistence, as other similar European forest (Dölle et al 2017). On the other hand, if human perturbation continues, together with climate change, Q. delgadoana could replace F. grandifolia subsp., mexicana, because the oak species was the second most important canopy tree, with the highest seedling density and is the dominant species in the adjacent oak forest.…”
Section: Discussionmentioning
confidence: 98%
“…ing through because it facilitates the entry of seeds, mainly herbs, from nearby disturbed sites such as pasturelands and agricultural areas, active or abandoned. On the other hand, the diversity of seedling is higher under canopy with greater tree-layer diversity in a beech-oak forest, while that in Fagus sylvatica forest the herb-layer was principally dominated by juvenile beech (Dölle et al 2017). Thus, it would be expected that in conserved forests the relationship in biodiversity among structural components would be higher than in those disturbed by human activities within anthropized landscapes.…”
mentioning
confidence: 99%
“…However, relationships between overstorey tree diversity and understorey plant diversity remain unclear (Landuyt et al 2019). Some studies have shown that understorey plant assemblages and richness depend on tree canopy identity (Gamfeldt et al 2013; De Groote et al 2017; Dölle et al 2017) or diversity (Houle, 2007; Vockenhuber et al 2011). Other studies indicated that overstorey tree species richness affects understorey species composition but not richness (Ampoorter et al 2014), increased shrub layer diversity but not herb layer diversity (Gazol and Ibáñez, 2009), or simply does not influence understorey species diversity (Ewald, 2002; Both et al 2011; De Groote et al 2017).…”
Section: Introductionmentioning
confidence: 99%